Eldorado [videorecording (DVD)] - Bronckart, Jacques-Henri; Lanners, Bouli, 1965-; Adde, Fabrice; Roaux, Germinal (Film Movement series, 2009)
When Yvan, a quick-tempered 40-year-old vintage car dealer, catches young burglar and ex-junkie Elie trying to rob him, Yvan becomes strangely attached to Elie and agrees to drive him home to his parents in his old Chevrolet, leading to a bizarre journey through Belgium for the two loners.